Comparison of knee flexor strength recovery between semitendinosus alone versus semitendinosus with gracilis autograft for ACL reconstruction: a systematic review and meta-analysis - Angelo Matteucci; Johan Högberg; Ramana Piussi; Mathias Wernbom; Edoardo Franceschetti; Umile Giuseppe Longo; Kristian Samuelsson; Johan Lövgren; Eric Hamrin Senorski (BMC Musculoskeletal Disorders, 2024)
Abstract Background Whether there is a difference in harvesting the semitendinosus tendon alone (S) or in combination with the gracilis tendon (SG) for the recovery of knee flexor strength after anterior cruciate ligament (ACL) reconstruction remains inconclusive. Therefore, this study aimed to assess the recovery of knee flexor strength based on the autograft composition, S or SG autograft at 6, 12, and ≥ 24 months after ACL reconstruction. Methods A systematic review and meta-analysis was conducted following the PRISMA guidelines. A comprehensive search was performed encompassing the Cochrane Library, Embase, Medline, PEDRo and AMED databases from inception to January 2023. Inclusion criteria were human clinical trials published in English, comprised of randomized controlled trials (RCTs), longitudinal cohort-, cross-sectional and case–control studies that compared knee flexor strength recovery between S and SG autografts in patients undergoing primary ACL reconstruction. Isokinetic peak torques were summarized for angular velocities of 60°/s, 180°/s, and across all angular velocities, assessed at 6, 12, and ≥ 24 months after ACL reconstruction. A random-effects model was used with standardized mean differences and 95% confidence intervals. Risk of bias was assessed with the RoBANS for non-randomized studies and the Cochrane RoB 2 tool for RCTs. Certainty of evidence was appraised using the GRADE working group methodology. Results Among the 1,227 patients from the 15 included studies, 604 patients received treatment with S autograft (49%), and 623 received SG autograft (51%). Patients treated with S autograft displayed lesser strength deficits at 6 months across all angular velocities d = -0.25, (95% CI -0.40; -0.10, p = 0.001). Beyond 6 months after ACL reconstruction, no significant difference was observed between autograft compositions. Conclusion The harvest of S autograft for ACL reconstruction yields superior knee flexor strength recovery compared to SG autograft 6 months after ACL reconstruction, irrespective of angular velocity at isokinetic testing. However, the clinical significance of the observed difference in knee flexor strength between autograft compositions at 6 months is questionable, given the very low certainty of evidence and small effect size. There was no significant difference in knee flexor strength recovery between autograft compositions beyond 6 months after ACL reconstruction. Trial registration CRD42022286773.